(untitled) (The Review of Diabetic Studies, 2025)
Asphyxia represents a critical medical emergency requiring immediate and effective intervention by emergency medical personnel. This comprehensive review examines current evidence-based practices and emerging strategies for managing asphyxiation cases in pre-hospital settings, with specific focus on enhancing paramedic performance within emergency medical services frameworks. Through systematic analysis of contemporary literature and clinical protocols, this paper identifies key intervention strategies, common challenges, and practical solutions applicable to field emergency care. The research synthesizes findings from multiple international studies, clinical guidelines, and evidence-based protocols to establish a comprehensive framework for asphyxia management. Critical areas examined include initial assessment techniques, airway management strategies, ventilation protocols, advanced life support interventions, and scene safety considerations. The analysis reveals that successful outcomes in asphyxia cases depend heavily on rapid recognition, systematic assessment, and timely implementation of appropriate interventions. Furthermore, the research identifies significant gaps in current training programs and proposes enhanced educational approaches to improve paramedic competency. The findings emphasize the importance of regular skills maintenance, simulation-based training, and protocol adherence in optimizing patient outcomes. This paper provides actionable recommendations for emergency medical service providers, highlighting the necessity of continuous professional development, equipment standardization, and quality assurance mechanisms. The comprehensive approach presented offers practical guidance for paramedics managing asphyxia emergencies while contributing to the broader discourse on pre-hospital emergency care optimization.